The relationship between - naiema khodadady; farzaneh shikholeslami; shohreh ahmadi; aliyeh FARZAM; zahra sharif (Journal of Holistic Nursing and Midwifery)
Introduction: Schizophrenia is a common and chronic mental disorder. Many of ‎Schizophrenia clients for some reasons stop taking anti psychotic drugs which results in ‎relapse and repeated hospitalizations, inability to keep a job and stigmatization and it can ‎decrease their quality of life. In attention to the point that follow up care at home can effect ‎clients' QOL, this study is designed to surcey it.‎